DESIGN AND IMPLEMENTATION OF SINGLE PHASE INVERTER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Now a days due to industrialization, there is gap between demand and supply, therefore the need of electricity is increased and we use the electricity efficiently. We cannot store the electricity in AC form, so we store the energy in battery in the form of DC and then it converts into AC using inverter. In that project, we are design and implement the inverter bridge on single phase full and half bridge inverter with R and RL load In that project the PWM method can be used for the generation of the waveforms.